2021
DOI: 10.1039/d1sc01478a
|View full text |Cite
|
Sign up to set email alerts
|

Signature of the neighbor's quantum nuclear dynamics in the electron transfer mediated decay spectra

Abstract: We computed fully quantum nuclear dynamics, which accompanies electron transfer mediated decay (ETMD) in weakly bound polyatomic clusters. We considered two HeLi2 clusters -- with Li2 being either in the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Therefore, investigation of He + (1s –1 )M 2 (M = Na, K, and Rb) is necessary to understand the ETMD process in the He droplet environment in the presence of different alkali dimers, which will shed light on He impurity interaction. The ETMD , process, which leads to double ionization of the alkali dimer, can be described in the following general equation for homonuclear and heteronuclear dimers H e M 2 h ν normalH normale + ( 1 normals 1 ) M 2 normalE normalT normalM normalD H e ( 1 s ) 2 + normalM 2 2 + H e + M + + M + H e M N h ν normalH normale + ( 1 normals 1 ) M N normalE normalT normalM normalD H e ( 1 normals 2 ) + ( M …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, investigation of He + (1s –1 )M 2 (M = Na, K, and Rb) is necessary to understand the ETMD process in the He droplet environment in the presence of different alkali dimers, which will shed light on He impurity interaction. The ETMD , process, which leads to double ionization of the alkali dimer, can be described in the following general equation for homonuclear and heteronuclear dimers H e M 2 h ν normalH normale + ( 1 normals 1 ) M 2 normalE normalT normalM normalD H e ( 1 s ) 2 + normalM 2 2 + H e + M + + M + H e M N h ν normalH normale + ( 1 normals 1 ) M N normalE normalT normalM normalD H e ( 1 normals 2 ) + ( M …”
Section: Introductionmentioning
confidence: 99%
“…The ETMD process has been studied theoretically in hydrogen bonded clusters. 26,27 Recently, Ghosh et al 28 have investigated the ETMD process in the HeLi 2 cluster. Their investigation, has shown that multimode nuclear dynamics play a significant role in the ETMD process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Experimentally, the ETMD process has been observed in rare gas clusters and alkali doped helium droplets. Recently, Unger et al have investigated the ETMD process in LiCl aqueous solution. The ETMD process has been studied theoretically in hydrogen bonded clusters. , Recently, Ghosh et al have investigated the ETMD process in the HeLi 2 cluster. Their investigation, has shown that multimode nuclear dynamics play a significant role in the ETMD process.…”
Section: Introductionmentioning
confidence: 99%
“…The ETMD process has been studied theoretically in hydrogen bonded clusters. 26,27 Recently, Ghosh et al 28 have investigated the ETMD process in the HeLi 2 cluster. Their investigation, has shown that the multi-mode nuclear dynamics play a significant role in the ETMD process.…”
Section: Introductionmentioning
confidence: 99%